Improving susceptibility mapping using a threshold‐based K‐space/image domain iterative reconstruction approach. Issue 5 (26th June 2012) - Tang, J.; Liu, S.; Neelavalli, J.; Cheng, Y. C. N.; Buch, S.; Haacke, E. M.
Abstract To improve susceptibility quantification, a threshold‐based k‐space/image domain iterative approach that uses geometric information from the susceptibility map itself as a constraint to overcome the ill‐posed nature of the inverse filter is introduced. Simulations were used to study the accuracy of the method and its robustness in the presence of noise. In vivo data were processed and analyzed using this method. Both simulations and in vivo results show that most streaking artifacts inside the susceptibility map caused by the ill‐defined inverse filter were suppressed by the iterative approach. In simulated data, the bias toward lower mean susceptibility values inside vessels has been shown to decrease from around 10% to 2% when choosing an appropriate threshold value for the proposed iterative method. Typically, three iterations are sufficient for this approach to converge and this process takes less than 30 s to process a 512 × 512 × 256 dataset. This iterative method improves quantification of susceptibility inside vessels and reduces streaking artifacts throughout the brain for data collected from a single‐orientation acquisition. This approach has been applied to vessels alone as well as to vessels and other structures with lower susceptibility to generate whole brain susceptibility maps with significantly reduced streaking artifacts. Magn Reson Med, 2013. © 2012 Wiley Periodicals, Inc.